The systemic approach in sociology and Niklas Luhmann : expectations, discussions, doubts - Šubrt, Jiří (Emerald Publishing Limited, 2020)
This book is a comprehensive overview of the theoretical discussion of one of most important conceptions in sociology at the end of 20th century - the theory of social systems. The spotlight of this book falls on the work of Niklas Luhmann and his holistic approach. Current modern society is, for Luhmann, a functionally differentiated society, which means that a number of specialized societal sub-systems (politics, economics, religion, law, science, art etc) have formed. Each system is based on its own type of communication led by its own generalized communicative media. Luhmann controversially depicts modern society as a plurality of many societal subsystems operating without a top and without a coordinating and managing centre. This book weighs the strong and weak features of the systemic approach in sociology and discusses ways to rethink it.